Risk maker risk taker a manager's guide to risk - Bertsos, Nicholas; Smith, Jacqueline ([Rose Bay North, N.S.W.] : Nicholas and Smith, 2007)
This video will show managers throughout your organisation the steps to manage the risks in their environment. It will give them an insight into the cracks which can occur in the risk process which could threaten the organisation's ability to achieve its objectives, and in some cases its survival
DVD format
Keywords: Risk management -- Australia